Stenotic lesion level did not affect outcomes of carotid endarterectomy. (May 2017) - Suhara, Masamitsu; Hoshina, Katsuyuki; Akai, Atsushi; Isaji, Toshihiko; Akagi, Daisuke; Yamamoto, Kota; Miyahara, Takuya; Watanabe, Toshiaki
Background: Carotid endarterectomy is the established treatment for carotid artery stenosis, and remains the primary surgical option due to its superior outcomes compared to carotid arterial stenting. However, Japanese patients are known to have unfavorable anatomical conditions for carotid endarterectomy, with a relatively higher level of the carotid artery bifurcation than in the Western population. We investigated the outcomes of carotid endarterectomy in our institute and evaluated the procedural quality by comparing patients based on higher or lower lesion levels. Methods: The clinical data of 65 patients who underwent carotid endarterectomy were collected retrospectively. The outcomes reviewed included stroke-free survival and stroke-free rate. The patients were divided into a higher group ( n = 25) and a lower group ( n = 40), based on lesion location in respect of the 2nd cervical vertebral level. Results: There was no perioperative death and only one case of stroke in the higher group within 30 days after carotid endarterectomy. At 5 years after carotid endarterectomy, the stroke-free survival rates were 83.4% in the higher group and 87.8% in the lower group, while the stroke-free rates were 96.0% and 94.0%, respectively; there were no significant differences between groups. Conclusions: Stenotic lesion level did not affect the outcome or procedural quality of carotid endarterectomy.